RYTUAŁY PRZEJŚCIA, NADANIA I ZATWIERDZANIA W SPOŁECZNEJ PRZESTRZENI RODZINY (Z BADAŃ NAD MŁODZIEŻĄ) - Sroczyńska, Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Rituals are the social strategies focused on what is “sacred”, which function is consecrating the difference, as well in the religious, as social and cultural field. In this article had been taken the reflection on presence of celebrating rituals in the social area of family, taking into consideration (in the context of author´s researches) the opinions of youth on the threshold of adulthood and their life expectations. Young people have real or anticipated experiences of participation in actions may be recognized as religious rites de passage and these, with reference to conception of Pierre Bourdieu, which accept the forms of the rituals of granting (eg. “eighteen”), or corresponding with the rituals of endorsement (pre-graduation ball, secondary school-leaving examination). These three categories of rituals, although meet in social space of family, overcome it, entering under the influence of different socialization environments. This is an important ability of polish families to transmitting these values and patterns of activity, which testify a kind of generational continuity, as also create the ritual competitions allowing celebration what is included in sacrum sphere.